Efektivitas Lembar Kerja Peserta Didik (LKPD) terhadap Kemampuan Pemecahan Masalah Matematis : Sebuah Meta-Analisis berdasarkan Jenjang Pendidikan dan Bentuk LKPD - Abdur Rahman Hakim; Oktarisa Ramadhanti; Hilda Ladan Bijani; Rena Revita (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
Mathematical Problem-Solving Ability (KPMM) is one of the essential skills that must be developed, as it trains students to formulate appropriate solution strategies, understand the meaning of each step, and cultivate systematic thinking habits. One of the tools that can be utilized to support the development of KPMM is the use of Student Worksheets (LKPD). Various studies have demonstrated the effectiveness of using LKPD in improving students' KPMM; however, comprehensive reviews that specifically examine the effectiveness of LKPD based on educational level and the form of LKPD used are still limited. Therefore, this study aims to analyze and synthesize previous research findings on the effectiveness of LKPD in supporting students’ KPMM in terms of educational level and LKPD format through a meta-analysis method. The population and sample of this study consist of journal articles and national conference proceedings selected according to PRISMA guidelines. The results of the meta-analysis show that the use of LKPD has a very strong influence on enhancing students' KPMM, with an effect size of 2.123. Based on educational level, LKPD is proven to be more effective when used at the junior high school level (SMP) compared to the senior high school level (SMA), while in terms of format, digital LKPD is more effective than printed LKPD in supporting students' KPMM.